”GREEN” HRM: AN EVALUATION AND THE FUTURE AGENDA - Andreas W Gunawan Putra (Universitas Trisakti, 2011)
The application of “green” Human Resource Management Practices (HRMP) to achieve a company’s competitive advantage particularly in the hospitality industry is arguably derives fromits Human Resource Management strategy. This has been driven by both customer requirements and increasing intensity of competition. It seems essential these days to invest in quality of Human Resources in order to improve its competitive advantage. However, far from being investigated as the difficulty for the consistency and integrity of the application of ‘green’ HRMP in the workplace.Furthermore, a frame of reference for “Green” HRM has yet to emerge. It is suggested that “green”’ HRMP concepts and frameworks could be utilized to improve the hospitality industrymaintaining its green environment. This paper examines critical aspects of ‘green’ HRMP theory and practices to underpinning business service performance. Indeed, the paper suggests a research agenda that could begin to investigate these propositions.